Feasibility of optical surface-guidance for position verification and monitoring of stereotactic body radiotherapy in deep-inspiration breath-hold - Naumann, Patrick; Batista, Vania; Farnia, Benjamin; Fischer, Jann; Liermann, Jakob; Tonndorf-Martini, Eric; Rhein, Bernhard; Debus, Jürgen (Frontiers in oncology, 2020)
Background Reductions in tumor movement allow for more precise and accurate radiotherapy with decreased dose delivery to adjacent normal tissue that is crucial in stereotactic body radiotherapy (SBRT). Deep inspiration breath-hold (DIBH) is an established approach to mitigate respiratory motion during radiotherapy. We assessed the feasibility of combining modern optical surface-guided radiotherapy (SGRT) and image-guided radiotherapy (IGRT) to ensure and monitor reproducibility of DIBH and to ensure accurate tumor localization for SBRT as an imaging-guided precision medicine. Methods We defined a new workflow for delivering SBRT in DIBH for lung and liver tumors incorporating SGRT and IGRT with cone beam computed tomography (CBCT) twice per treatment fraction. Daily position corrections were analyzed and for every patient two points retrospectively characterized: an anatomically stable landmark (predominately Schmorl's nodes or spinal enostosis) and a respiratory-dependent landmark (predominately surgical clips or branching vessel). The spatial distance of these points was compared for each CBCT and used as surrogate for intra- and interfractional variability. Differences between the lung and liver targets were assessed using the Welcht-test. Finally, the planning target volumes were compared to those of free-breathing plans, prepared as a precautionary measure in case of technical or patient-related problems with DIBH. Results Ten patients were treated with SBRT according this workflow (7 liver, 3 lung). Planning target volumes could be reduced significantly from an average of 148 ml in free breathing to 110 ml utilizing DIBH (p< 0.001, pairedt-test). After SGRT-based patient set-up, subsequent IGRT in DIBH yielded significantly higher mean corrections for liver targets compared to lung targets (9 mm vs. 5 mm,p= 0.017). Analysis of spatial distance between the fixed and moveable landmarks confirmed higher interfractional variability (interquartile range (IQR) 6.8 mm) than intrafractional variability (IQR 2.8 mm). In contrast, lung target variability was low, indicating a better correlation of patients' surface to lung targets (intrafractional IQR 2.5 mm and interfractional IQR 1.7 mm). Conclusion SBRT in DIBH utilizing SGRT and IGRT is feasible and results in significantly lower irradiated volumes. Nevertheless, IGRT is of paramount importance given that interfractional variability was high, particularly for liver tumors.